Effects of the Energy Communities: A Case of Application in Colombia - Hoyos, Santiago; Ruíz, Sebastián; Montoya Rendón, Andrés Felipe; Gutiérrez, Yesika; Barrientos Marín, Jorge Hugo; Ramìrez, Mauricio Alviar (International Journal of Energy Economics and Policy, 2026)
This article examines the environmental and economic effects of energy communities, considering both short- and long-term impacts. For the long-term analysis, a simulation model was developed to observe the behaviour of variables within the electricity market and their impacts over a 20-year evaluation period. The environmental impact was quantified through avoided emissions in Mt of CO₂ equivalent. In economic terms, the savings from self-generation and the expected revenues from surplus energy sales were calculated, alongside a profitability analysis per user. The results indicate that energy communities could avoid 25 MtCO₂e, while the regulated market could achieve savings 18.5 Billion USD, in addition to potential revenues of 2 Billion USD. These outcomes arise from the aggregated implementation of photovoltaic systems in households and small businesses within the framework of energy communities.